The Influence of Service Quality and Price on Consumer Satisfaction at Okinawa Sushi Pakuwon Mall Surabaya City - Rhiza Aurillia Rachmawati; Damajanti Sri Lestari; Hadi Sugiyanto (Cita konsultindo, 2025)
Competition in the restaurant industry is getting tighter, especially in premium shopping centers such as Pakuwon Mall, Surabaya. This research aims to analyze the influence of service quality and price on consumer satisfaction at Okinawa Sushi. The research method used was quantitative with a causal approach, involving 100 respondents using a purposive sampling technique. Data analysis was carried out using multiple linear regression tests. The research results show that service quality and price have a significant effect on consumer satisfaction, both partially and simultaneously. Apart from that, the price variable has a more dominant influence compared to service quality. These findings provide implications for restaurant management in improving service strategies and pricing policies to maintain customer loyalty in the premium restaurant segment.